Pelaksanaan Pembelajaran PJOK di SMP Negeri Se-Kecamatan Boja Selama Masa Pandemi Covid-19 Tahun 2021 (Indonesian Journal for Physical Education and Sport, 2022)
Physical education learning utilizes physical activity for the learning process. Physical education learning is mostly carried out outside the classroom, this becomes different when theoutbreak Covid-19occurs and the implementation changes to online learning. For this reason, the problem in this research is how to plan, implement and evaluate Physical education learning at State Junior High Schools throughout the Boja District before and during the Covid-19 pandemic. The purpose of this study is to describe and examine the planning, implementation and evaluation of Physical education learning at State Junior High Schools throughout the Boja District before and during the Covid-19 pandemic. This research is a type of qualitative research with a descriptive approach. The results of this study are that learning planning is carried out by compiling a syllabus and lesson plans, the implementation of learning is carried out with an online system through the media of google classroom and whatsapp, the evaluation of learning is carried out by assessing 3 aspects, namely the addictive, cognitive and psychomotor aspects. The conclusion of this study is that teachers continue to develop lesson plans, curriculum, time allocation and learning media before and during the different pandemic periods, assessments are carried out online with the same aspects as before thepandemic Covid-19.